2022
DOI: 10.3390/jpm12081311
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Robotic Video-Assisted Thoracoscopic Surgery Compared to Open Thoracotomy for Resectable Non-Small Cell Lung Cancer

Abstract: (1) Background: Conventional open thoracotomy has been the accepted surgical treatment for resectable non-small cell lung cancer. However, newer, minimally invasive approaches, such as robotic surgery, have demonstrated similar safety and efficacy with potentially superior peri-operative outcomes. The present study aimed to quantitatively assess these outcomes through a meta-analysis. (2) Methods: A systematic review was performed using electronic databases to identify all of the relevant studies that compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…A minimally invasive approach decreases mortality, hospital stay, overall postoperative complications, post‐operative transfusion requirement, pneumonia, atelectasis, chest drain duration and atrial arrhythmia compared to open thoracotomy . 9 …”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…A minimally invasive approach decreases mortality, hospital stay, overall postoperative complications, post‐operative transfusion requirement, pneumonia, atelectasis, chest drain duration and atrial arrhythmia compared to open thoracotomy . 9 …”
Section: Figmentioning
confidence: 99%
“…A minimally invasive approach decreases mortality, hospital stay, overall postoperative complications, post-operative transfusion requirement, pneumonia, atelectasis, chest drain duration and atrial arrhythmia compared to open thoracotomy . 9 We believed our patient was ideal for a robotic-assisted procedure, as she required both an abdominal and thoracic approach. The three-dimensional imaging and superior dexterity of the robotic platform enabled excellent visualization of the major vascular structures during liver mobilization.…”
mentioning
confidence: 99%
“…Potential drawbacks of the open approach are prolonged hospital stay, unappealing cosmetic results, delayed return to baseline activities, and potential wound-healing delays or complications among patients with diabetes and those who are immunocompromised. 3 In recent years, the introduction of minimally invasive ectopic parathyroid resection offered faster postoperative recovery, better cosmesis, and fewer complications than were associated with open surgery. In their case series, Alesina et al concluded that resection of thoracic ectopic parathyroid via video-assisted thoracoscopic (VATS) approach is a safe alternative.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the poor awareness of health check-ups among some people, the large economic disparity across the country and the lack of timely detection and diagnosis of patients in less developed areas due to various factors, the vast majority of patients in China are diagnosed at an advanced stage of lung cancer. Patients with advanced lung cancer are often accompanied by metastases to distant organs with large tumour sizes and multiple lymph node metastases [ 3 ]. Liver, bone, and brain metastases are common in patients with advanced lung cancer, and when brain metastases occur, the median survival time (overall survival, OS) of patients is only 1 month if they are not treated effectively [ 4 ].…”
Section: Introductionmentioning
confidence: 99%